Keterampilan Menulis Teks Deskripsi Dalam Pembelajaran Bahasa Indonesia Sekolah Dasar - Nazla Asyifa; Putri Azizah; Valen Tania (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Writing descriptive text is an activity carried out by someone in telling or describing a particular object so that the reader will be able to know clearly what the general description of the object being discussed is. At the elementary school level, when learning Indonesian, writing descriptive texts is one of the learning achievements that must be achieved by students. The development of descriptive text writing skills can be achieved using the problem based learning method so that it allows students to think critically during learning so as to improve student learning outcomes.